The brightest star in the sky [large type] - Keyes, Marian (Thorndike Press large print core, 2010)
The lives of seven Dublin neighbors become entangled when a sassy and prescient spirit pays a visit to their town house with the intent of changing at least one of them. But whose life will be transformed? Newlyweds Matt and Maeve, facing the first obstacle in their romance; Lydia the brassy cabbie with a passion for her flatmate; Katie the just-turned-forty PR executive; or the eldest resident Jemima currently playing hostess to her son Fionn?